Зовнішньополітичні орієнтири України у геополітичних візіях Дмитра Андрієвського - Стародуб, Тарас; Starodub, Taras (Видавництво Львівської політехніки, 2019)
Проаналізовано геополітичні візії Дмитра Андрієвського щодо зовнішньополітичних орієнтирів України, її геополітичного позиціонування і у регіоні Східної Європи, і у масштабах широкого діапазону міжнародної політики. У своїх геополітичних візіях Д. Андрієвський надає Україні місце регіонального лідера Східної Європи, стабільного та надійного безпекового центру на східних кордонах Європейського співтовариства супроти агресивної політики Москви. Історичним призначенням України є місце надійного посередника в політичних, економічних та культурних взаємовідносинах між Сходом та Заходом, інтеграційного та мобілізаційного осередку для своїх сусідів на сході Європи у формуванні спільної політичної та оборонної стратегії у стримуванні російської агресії. З метою висвітлення та аналізу геополітичних візій Андрієвського використано методи історизму, порівняльно-аналітичний та структурно-системний аналізи.

The purpose of this work is to analyze Dmytro Andrievsky’s geopolitical vision in terms of Ukraine’s foreign policy objectives and its geopolitical positioning in both Eastern Europe and broader range of international politics. The work is carried out using the following scientific methods: method of historicism, comparative and analytical methods, and structured systems analysis. The relevanace of this topic is based on the fact that in today's international realities of the Russian military intervention in Ukraine and the struggle for actual geopolitical leadership in Eastern Europe, Dmytro Andrievskyi’s geopolitical vision is still relevant and demanded. In his geopolitical vision, Andrievsky gives Ukraine the position of a regional leader of Eastern Europe and also a stable and reliable security center on the European community eastern borders against Moscow's aggressive policy. The historical assignment of Ukraine is a reliable mediator position in the political, economic and cultural relations between East and West, an integration and mobilization center for its natural neighbors in eastern Europe in shaping a common political and defensive strategy in deterring Russian aggression. Andrievsky definitely sees Ukraine within the European Community with an international mission of an active and effective political factor, which should work intensively in order to re-establish leadership in the geopolitical space between the Baltic Sea and the Black Sea, and thereby establish its control and impact on international politics in the Eastern and Central Europe.
Ukraine’s foreign policy guidelines in the geopolitical vision of Dmytro Andrievsky (20’s–30’s of the XX century)
Keywords: міжнародна політика; геополітика; націоналізм; Європейське співтовариство; Українська держава; Дмитро Андрієвський; international politics; geopolitics; nationalism; European community; Ukrainian state; Dmytro Andrievsky; 321 (477.8)